PENGEMBANGAN AROMA DAN CITA RASA BAKSO DENGAN MENGGUNAKAN FLAVOR [Development of Aroma and Taste of Meat Ball Using Flavor] - Joko Hermianto; . Aulia (Jurnal Teknologi dan Industri Pangan, 2001)
Bakso is one of the most popular meat product in Indonesia. This research studied of effect of addition of falvor to the quality of meat ball. The analysis included physical characteristics (specific gravity, hardness, shear, elasticity and color organoleptic test). The results showed that : according to consumer preference, the most like flavour that added in the meat ball were the flavour of beef Q. 1.%, beef Q 1.5%, Beef WIN 1.5% and beef Fat WIN 1.0%. the use of flavor did not cause differences in physical characteristics like specific gravity, hardness, shear, alasticity and color a-value. The use flavour in creased the price of bakso between Rp 4.5,- to Rp 18,-. According to comparison test, meat ball with beef Q 1.5% has the best score compared with Bakso Lapang Tembak (BLT) in aroma, and with Bakso Pedagang Keliling (BPK) has the best score in aroma, test and texture.